Bezpośrednie inwestycje zagraniczne a innowacyjność polskiej gospodarki - Stawicka, Magdalena (Foreign Direct iIvestment and the Innovation Economy in Poland, 2008)
The main purpose of the article is to show the influence of foreign direct investments on development of the innovation economy in Poland. The autor presented FDI inflows into Poland in 2005, the position of Poland among the European Union countries, the next expenditures on innovation activity by sectors, ownership forms and voivodships.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 12, s. 195-205